2021
DOI: 10.1038/s41522-021-00212-9
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of bacterial and fungal microbiomes in the gut of adult honeybees

Abstract: The core gut microbiome of adult honeybee comprises a set of recurring bacterial phylotypes, accompanied by lineage-specific, variable, and less abundant environmental bacterial phylotypes. Several mutual interactions and functional services to the host, including the support provided for growth, hormonal signaling, and behavior, are attributed to the core and lineage-specific taxa. By contrast, the diversity and distribution of the minor environmental phylotypes and fungal members in the gut remain overlooked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 132 publications
6
42
2
Order By: Relevance
“…The collection of recent results supports the existence of a rare fungal community that populates the gut of honey bee workers [46,47,69]. In agreement with another recent study [69] we found a strong relationship between bacterial and fungal density throughout the alimentary tract in the colony control, perhaps a reflection of broad changes in gut pH and oxygen (Fig.…”
Section: Fungal Relationshipssupporting
confidence: 92%
See 2 more Smart Citations
“…The collection of recent results supports the existence of a rare fungal community that populates the gut of honey bee workers [46,47,69]. In agreement with another recent study [69] we found a strong relationship between bacterial and fungal density throughout the alimentary tract in the colony control, perhaps a reflection of broad changes in gut pH and oxygen (Fig.…”
Section: Fungal Relationshipssupporting
confidence: 92%
“…Under normal conditions, or when colonized by a "conventional" microbiota, the central region of the ileum becomes anoxic whereas oxygen remains detectable in the center and periphery of "germ free" bee ileums fed sterile pollen [4]. Data on foragers suggests this relationship may be variable or change with age or diet [69]. Strongly allied with the host epithelium, S. alvi contributes to biofilm life, including SCFA and siderophore production [38,70].…”
Section: Transmission and Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…S2 in the supplemental material), suggesting that the particular combination of species and strains determines the extent of protection, as observed in studies with bumble bees ( 45 47 ). Bee guts can also contain yeasts, which are acquired from environmental sources and vary seasonally and between hives ( 48 , 49 ). These fungi may affect host immune function ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The total DNA extraction of crab gills was performed using 50 mg of gill tissue and a DNeasy Blood and Tissue Kit (Qiagen, Hilden, Germany) following the manufacturer’s protocol. Absolute abundances of the number of copies of the bacterial 16S rRNA gene were determined using the Eub338/Eub518 primer-set (specific for eubacteria Domain) as described by Frierer and colleagues [ 39 ] and Callegari and colleagues [ 40 ]. To obtain the standard gene of interest, the fragment was amplified from environmental DNA (size ± 180 bp).…”
Section: Methodsmentioning
confidence: 99%